1998
DOI: 10.1242/dev.125.11.2159
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsal-related immunity factor (Dif) can define the dorsal-ventral axis of polarity in the Drosophila embryo

Abstract: In Drosophila embryos, dorsal-ventral polarity is defined by a signal transduction pathway that regulates nuclear import of the Dorsal protein. Dorsal protein's ability to act as a transcriptional activator of some zygotic genes and a repressor of others defines structure along the dorsal-ventral axis. Dorsal is a member of a group of proteins, the Rel-homologous proteins, whose activity is regulated at the level of nuclear localization. Dif, a more recently identified Drosophila Rel-homologue, has been propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Only the dl gene, however, is expressed in the early embryo where it regulates dorsoventral patterning. Recently, Stein et al (1998) have shown that maternal expression of dif can partially rescue embryos from the consequences of a dl mutation, suggesting that DIF can partially substitute for Dl in this context. Furthermore, these experiments showed that dldeficient embryos rescued by dif exhibited dorsoventral polarity, which indicates that in these conditions DIF remained sensitive to the dorsoventral signaling cascade transmitted through Tl.…”
Section: Discussion Either Dif or DL Control The Expression Of The Dr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Only the dl gene, however, is expressed in the early embryo where it regulates dorsoventral patterning. Recently, Stein et al (1998) have shown that maternal expression of dif can partially rescue embryos from the consequences of a dl mutation, suggesting that DIF can partially substitute for Dl in this context. Furthermore, these experiments showed that dldeficient embryos rescued by dif exhibited dorsoventral polarity, which indicates that in these conditions DIF remained sensitive to the dorsoventral signaling cascade transmitted through Tl.…”
Section: Discussion Either Dif or DL Control The Expression Of The Dr...mentioning
confidence: 99%
“…Only the dl gene, however, is expressed in the early embryo where it regulates dorsoventral patterning. Recently, Stein et al . (1998) have shown that maternal expression of dif can partially rescue embryos from the consequences of a dl mutation, suggesting that DIF can partially substitute for Dl in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B and table S1). Spz is a secreted cytokine and a ligand for the Toll receptor in innate immunity and in embryonic dorsoventral patterning (30,(33)(34)(35). However, RNA interference (RNAi)-mediated knockdown of Toll itself (Toll-1) had little effect on competition (fig.…”
Section: Activation Of Innate Immune Pathways In Cell Competition Inv...mentioning
confidence: 99%
“…It also remains an open question as to whether the NF-ΚB factors have other transcriptional targets unrelated to the immune response that could be responsible. This is especially true for dif , who has additional developmental patterning roles during embryogenesis [53] and whose brains are ∼10% larger than wildtype.…”
Section: Discussionmentioning
confidence: 99%